Sustainable Innovation: Applying Permaculture Architecture in the Mocaf Factory Design in Banjarnegara - Bahy, Fairuz Naufal; Marlina, Endy; Ratriningsih, Desrina (Jurnal Internasional Teknik, Teknologi dan Ilmu Pengetahuan Alam, 2024)
Banjarnegara, a district in Central Java, possesses abundant natural resources suitable for cassava farming. However, the long distribution chain and the closure of several tapioca factories have significantly reduced the economic value of cassava in the region. To address this issue, this study aims to design a sustainable Modified Cassava Flour (Mocaf) industry using permaculture principles, focusing on resource efficiency, community welfare, and environmental sustainability. Mocaf flour, derived from fermented cassava, serves as an innovative substitute for wheat flour and supports regional food security. This research employs a descriptive method, which includes literature review, site surveys to evaluate land potential and accessibility, comparative studies, and analyses based on Permaculture Architecture principles. The factory design integrates sustainable strategies such as energy efficiency, waste management, and optimal resource utilization. Key features include zoning for production, storage, and waste treatment to streamline workflows and minimize environmental impacts. Solar panels are incorporated to enhance energy efficiency, while a wastewater treatment plant (IPAL) produces biogas from fermentation waste as part of an independent energy system. The proposed factory design highlights the principles of permaculture by emphasizing sustainability, resource efficiency, and harmony with the local ecosystem. By focusing on increasing local food production and minimizing environmental degradation, the design provides a model for sustainable industrial development and supports regional economic resilience.